2014 Triennial Surveillance Review : Concept Note. (Policy Papers; Policy Paper ;, 2013)
With the 2011 TSR laying out a wide ranging agenda for surveillance reform, the 2014 review will take a more narrowly focused approach and be mindful of the need to make cost-neutral recommendations. The themes and associated outputs will cover areas that address the IMF's core mandate of ensuring the stability of the international monetary system, provide the most value-added for the membership, and leverage the Fund's comparative advantages. The review will be based on: (i) a review and analysis of Article IV reports and multilateral surveillance products; (ii) guidance from an External Advisory Group at key stages of the exercise; (iii) background studies; and (iv) surveys and interviews with country authorities, staff, and other stakeholders. A review of the Financial Sector Assessment Program (FSAP) will be conducted separately but concurrently with the TSR, with close coordination between the relevant authoring teams. The TSR will also take into account the findings of other recent work, including the progress report on the implementation of the Financial Surveillance Strategy, the range of papers on debt issues, the LIC pilot on financial depth and macroeconomic policy, the set of Board papers on the experience with unconventional monetary policies and the challenges of exit from these policies, and the planned discussion of communication issues with the Executive Board.